The Influence of Competency and Quality of Work Life on Organizational Commitment with Job Satisfaction as a Mediating Variable: A Study of Civil Servants at the Education Office of Banjarmasin, Indonesia - Mailisa Irhamna; Rahmawati, Rini (HM Publisher, 2023)
Organizations around the world face challenges in their efforts to maintain and improve work productivity and efficiency. In this context, it is important for organizations to understand the factors that affect employee commitment to the organization while improving the quality of their work life. This study is a quantitative descriptive research. The sample in this study were all civil servants who worked at the education office of Banjarmasin, totaling 86 people. The sampling technique used is saturated sampling or census. This study was measured using PLS-SEM analysis. Competence has no significant positive effect on job satisfaction in civil servants at the education office of Banjarmasin. The quality of work life has a significant positive effect on job satisfaction in civil servants at the education office of Banjarmasin. Competence has a significant positive effect on organizational commitment in civil servants at the education office of Banjarmasin. The quality of work life has a significant positive effect on organizational commitment in Civil Servants at the education office of Banjarmasin. Job satisfaction has no significant positive effect on organizational commitment to civil servants at the education office of Banjarmasin. Job satisfaction cannot mediate competency in organizational commitment in civil servants at the education office of Banjarmasin. Job satisfaction cannot mediate the quality of work life on organizational commitment in civil servants at the education office of Banjarmasin.